CLUE Chemistry, Life, the Universe and Everything - Cooper, Melanie M.; Klymkowsky, Michael W.; Open Textbook Library (Open Textbook Library, 2016)
This text is intended to provide an in-depth introduction to the key ideas in chemistry. We have designed the book to show how these ideas are developed from simple to complex systems and how they relate to each other. We consider three ideas central to an understanding of chemistry: the structure of matter, the properties of matter, and the energy changes involved in the reorganization of matter; all are connected by the interactions or forces that cause matter to interact. We aim to provide compelling reasons why you will find yourself wanting to learn chemistry and to illustrate what you will be able to do with this knowledge once you have learned it.
1. Atoms -- 2. Electrons and Orbitals -- 3. Elements, Bonding, and Physical Properties -- 4. Heterogeneous Compounds -- 5. Systems Thinking -- 6. Solutions -- 7. A Field Guide to Chemical Reactions -- 8. How Far? How Fast? -- 9. Reaction Systems
In English.
Description based on online resource
Keywords: Chemistry -- Textbooks